Influence of interlayers on the interdiffusion under conditions of martensitic transformations - Koval, Yu.N.; Mazanko, V.F.; Gertsriken, D.S.; Bogdanov, E.I.; Mironov, V.M.; Bogdanov, S.E. (Reports of the National Academy of Sciences of Ukraine, 2021)
The phase composition of the diffusion zone formed under the low-temperature impulse exposure is investigated by methods based on the use of radioactive indicators, X-ray structural and microdurometric analyzes. Deformation was treated by means of using the significant bulk effect during the athermal martensite transformations (γ→ α at the liquid nitrogen cooling and γ→ α at the heating up to 923 K). The iron alloy with 30 % nickel content existed after various conditions of preliminary treatment at room temperature in a homogeneous solid solution in two kinds: bcc lattice (α-phase) and fcc lattice (γ-phase). There were made the cubic samples from fcc lattice and П-shaped ones (the Greek letter alphabet) from bcc lattice ones. The surfaces of cubic samples were covered with the layers of labeled atoms and placed into П-like ones. Between these layers and parallel surfaces of the lower part were two foils [iron and molybdenum (or nickel, copper, aluminum)] in order to ensure the contact between all kinds of the researched materials. Jointed samples were dipped into liquid nitrogen (transformation occurs in the cubic sample) or placed into a heated oven at 923 K (transformation occurs in the П-shaped one). The bulk effect during these transformations stimulates a pulse deformation of the contacting surfaces and near-surface layer in both cases. The present load scheme allows one to obtain samples to be undergone to a pulse deformation action and a simultaneous action γ ⇄ a transformations and plastic deformations made by them. The control samples underwent γ→ α and α → γ transformations without interlayers. In ad dition, they underwent transformations without additional pulse deformation. The influence of intermediate layers on the rate of mass transfer and the features of the phase formation under conditions of martensitic transformations with the explosive kinetics is shown. The relationship between the type of penetrating atoms and the phases they form under nonequilibrium conditions has been established.